DESAIN MASJID LINGKUNGAN DI DESA WOLOAN, KOTA TOMOHON - MANADO - Previari Umi Pramesti (Sekolah Vokasi Universitas Diponegoro, 2020)
This journal discusses how to do the mosque design process in an environment that is predominantly non-Muslim as well as extreme contours. The majority of Manado residents are Christians, while Islam is the 2nd largest religion. However, the existence of mosques in the city of Manado itself is still too little. Some areas in Manado are tourist areas, including Woloan Village which is a center for the wooden house industry and the trans route to Tomohon. This area is potential enough to build an environmental mosque to support the worship activities of residents and visitors to the area. The method used is a qualitative approach to the needs of the mosque and SWOT analysis. The purpose and aim of this service and research is to produce a mosque design that is in accordance with the conditions and potential of the area. The products produced are the design and working drawings of the mosque.